Photoreceptor Degeneration in Pro23His Transgenic Rats (Line 3) Involves Autophagic and Necroptotic Mechanisms - Kakavand, Kiana; Jobling, Andrew I.; Greferath, Ursula; Vessey, Kirstan A.; de Iongh, Robb U.; Fletcher, Erica L. (Frontiers in Neuroscience, 2020)
Photoreceptor death contributes to 50% of irreversible vision loss in the western world. Pro23His (P23H) transgenic albino rat strains are widely used models for the most common rhodopsin gene mutation associated with the autosomal dominant form of retinitis pigmentosa. However, the mechanism(s) by which photoreceptor death occurs are not well understood and were the principal aim of this study. We first used electroretinogram recording and optical coherence tomography to confirm the time course of functional and structural loss. Electroretinogram analyses revealed significantly decreased rod photoreceptor (a-wave), bipolar cell (b-wave) and amacrine cell responses (oscillatory potentials) from P30 onwards. The cone mediated b-wave was also decreased from P30. TUNEL analysis showed extensive cell death at P18, with continued labelling detected until P30. Focused gene expression arrays indicated activation of, apoptosis, autophagy and necrosis in whole retina from P14-18. However, analysis of mitochondrial permeability changes (ΔΨm) using JC-1 dye, combined with immunofluorescence markers for caspase-dependent (cleaved caspase-3) and caspase-independent (AIF) cell death pathways, indicated mitochondrial-mediated cell death was not a major contributor to photoreceptor death. By contrast, reverse-phase protein array data combined with RIPK3 and phospho-MLKL immunofluorescence indicated widespread necroptosis as the predominant mechanism of photoreceptor death. These findings highlight the complexity of mechanisms involved in photoreceptor death in the Pro23His rat model of degeneration, and suggest therapies that target necroptosis should be considered for their potential for reducing photoreceptor death.